5th European conference of ACENDIO - association for common european nursing diagnoses, interventions and outcomes - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
Documenting Nursing CareEnhancing patient care through nursing documentation: new directions for novices and experts7-9 April 2005, Festival Hall – Convention Centre Bled - Bled – Slovenia ACENDIO has great pleasure in inviting you toBled,Slovenia, for the fifth biennial European Conference of the Association for Common European Nursing Diagnoses, Interventions and Outcomes (ACENDIO). Our theme for this conference is ‘Documenting Nursing Care – Enhancing patient care through nursing documentation: new directions for novices and experts’. The focus of the Bled conference is to demonstrate the practical and political use of nursing documentation for the enhancement of patient care. Also to communicate the usefulness of terminologies and classifications, and the results of nursing data collection for nursing practice. We would therefore like to invite you to submit your work in this field in the form of an abstract to the chair of the scientific committee.Submission of abstractsThe official language of the pre-conference is Slovenian, and for the main conference English. Simultaneous translation in English, French, German and Slovenian will be provided for the pre-conference and all plenary sessions in the main hall. For the main conference we invite you to submit abstracts according the following instructions / information:1. Submit your abstract before 15 August2004 inan electronic way, either by e-mail or by diskette.2. Abstracts can be submitted in one of the following three languages: English, French or German. However, if accepted, the presentation needs to be presented in English.3. The following format should be used:Font Arial, Times New Roman or equivalent, size 11 point and one line spacingType the title of presentation in CAPITAL LETTERSIndicate the preferred form of presentation: oral presentation / poster presentation / workshop or seminarType name(s) of author(s) preceded by initials: omit titles, degrees, etc..Underline the name of the main presenterType private post-mail address, e-mail address, and phone-fax number of main presenter, orType name of institution, post-mail address, e-mail address, and phone-fax number where the main presenter is working (only one contact address)4. The abstract should contain:· (1) A summary and keywords of the abstract content in English of not more than 50 words. Please also indicate which conference theme your abstract relates to.· (2) The main abstract, which should not exceed more than 500 words·State specific objective(s) of study or project, methods and results, but avoid tables, diagrams and footnotes if possible.·Submissions may report original research, project development / evaluation, practice applications or position papers, but should always relate to the theme(s) of the conference.·All submissions will be acknowledged on receipt5. Theme(s) of the conference:Enhancing patient care through nursing documentationImplementing nursing diagnoses, interventions and outcomesExamples of using nursing diagnoses, interventions and outcomes in practiceDevelopment of specific nursing diagnoses, interventions and outcomesTeaching the use of nursing diagnoses, interventions and outcomesDevelopment of nursing terminology  / classification systems.Examples of nursing languages within electronic patient documentationFrom nursing data collection to information / policy, examples of nursing data sets, and of integration of nursing data into (inter)national health data sets6. The scientific committee will recommend abstracts for acceptance either as oral or poster presentation, workshop or seminar to the board of ACENDIO. Authors will be notified by 4 October 2004 of time, date and method and allocation of presentation. Submission of an abstract implies registration for the conference, and acceptance of the final decision about method and allocation of presentation by the board of ACENDIO, and therefore no further correspondence will be entered into. You are also required to register before 31st of December 2004. Providing you register before this date, the main presenter will be eligible for a 10%deduction on the registration fee.7. If the abstract is accepted for an oral presentation you will be required to send in a fuller version of the paper presentation with adequate reference to the literature by 15 November 2004 for printing in the proceedings of the conference. The full paper should not exceed 6 pages, A4 size, 1,5 line spacing, including possible tables, diagrams, footnotes, and literature references.8. Please submit your abstract before 15 August 2004 => 1 September !!!! to:Prof. Dr. Walter Sermeus, chair ACENDIO scientific committeeACENDIO Conference Managementc/o Oud Consultancy & Conference ManagementHakfort 6211102 LAAmsterdamTheNetherlandsE-Mail: conference.management@freeler.nl9. Schedule :Submission deadline 15 August 2004 => 1 September !!!Notification of acceptance 4 October 2004Submission full paper for conference proceedings 15 November 2004Registration for conference before 31 December 2004  For further information about the programme, please look at www.oudconsultancy.nlOud Consultancy & Conference ManagementHakfort 6211102 LAAmsterdamTheNetherlandsTel: ++ 31 (0)20 409 0368Mob: ++ 31 (0)653941506Fax: ++ 31 (0)20 409 0550E-mail: conference.management@freeler.nl